Youth and Politics in Democratic Argentina: Inventing Traditions, Creating New Trends (1983-2008) - Chaves, Mariana (2012)
This paper has three objectives of different caliber. First, to present the trajectories of youth studies- in particular about youth and politics- in Argentina from 1983 to 2008, within the political and academic local context. Second, to present our study on youth and politics through several cases of youth participation. Finally, to discuss youth and politics as an academic and societal preoccupation in the light of the afore-mentioned processes.